Finite Control Set Based On The Voltage Vector Representation Of Switching State - Kozubík, Michal (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2021)
This paper introduces novel approach in the implementing of finite control set modelpredictive control for the permanent magnet synchronous motor. This approach is based on the pregeneratingof voltage vectors based on the specific switching state of voltage source inverter. Thelimitation of the pre-generating is based on the resolution of encoder used to measure mechanicalangle of rotor. Proposed algorithm is described and tested in PIL simulation using Jetson Nano, forthe control algorithm execution, and Simscape model of motor.
Keywords: finite control set; model predictive control; voltage vectors; optimization; general-purposecomputing